Causation in Section 15 of the Property (Relationships) Act 1976: Analysing the New Zealand Supreme Court’s "Working Assumption" - Is it Really Working? - Haradasa, Tasneem (Victoria University of Wellington Law Review, 2019)
Scott v Williams concerned s 15 of the Property (Relationships) Act 1976. In situations of significant economic disparity post-separation, s 15 empowers courts to depart from the default rule of equal division of relationship property to compensate the disadvantaged partner. Causation is one of the jurisdictional hurdles. Only disparity "because of" the division of functions (DOF) is compensable. Thus far, courts have adopted a strict causation approach by placing a costly and often unattainable evidential burden on claimants. Consequently, compensation has been beyond reach for deserving claimants. Responding to this disquiet, Scott’s majority propounded a "working assumption" of causation in relationships conducted along traditional lines, where one party assumes primary responsibility for domestic duties and the other for income-earning. In such situations, Scott’s majority would assume causation at jurisdiction and attribute the entire disparity to the DOF when determining the quantum award. This article concludes that the working assumption is a positive development in terms of jurisdiction. However, unlike the majority, it argues that striking the correct balance between s 15’s "because of" wording and broad policy rationale requires an apportionment of causes at quantum. Furthermore, Scott’s "traditional lines" and "non-career partner" terminology creates unnecessary confusion and should be eschewed.